Potential Of Albizzia Forest in Food Crops Based Agroforestry - Indah Rekyani Puspitawati; Anang Susanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Management of State-owned forests needs to involve the community in utilizing the area. One of them is that the community around the forest area is given authority to obtain permission to manage the forest. Efforts were made to get legalization for the community in accessing and managing forest areas; the government issued a social forestry policy. Management of forest areas using a regime management system requires the participation of communities around the site, so it is necessary to be more active in managing agroforestry-based land. The primary aim of this research is to determine the potential of the Albizzia forest in helping the community provide arable land for agriculture in the development of an agroforestry system. The data collection technique used in this research is field observation, with interview techniques carried out directly. Farmers' responses (77%) of farmers who have introduced this system stated that they were delighted, (19%) answered that they were not happy, and 4% said they were satisfied. Farmers' satisfaction with this management system is seen as a local community product that has proven effective in dealing with economic changes in communities around the Albizzia forest area